Exosomes and cells from lung cancer pleural exudates transform LTC4 to LTD4, promoting cell migration and survival via CysLT1. (1st March 2019) - Lukic, Ana; Wahlund, Casper J.E.; Gómez, Cristina; Brodin, Daniel; Samuelsson, Bengt; Wheelock, Craig E.; Gabrielsson, Susanne; Rådmark, Olof
Abstract: Tumor-derived exosomes can modulate the cancer microenvironment and induce metastatic spread. Exosomes may carry enzymes for leukotriene (LT) biosynthesis, but the role of exosomal LTs has not been studied in cancer. We isolated exosomes and malignant cells from pleura exudates from 14 patients with non-small cell lung cancer. Lipidomic profiles, migration and apoptosis were determined. Both exosomes and primary cancer cells contained γ-glutamyl transpeptidase 1 (GGT-1) and avidly transformed exogenous LTC4 to pro-tumorigenic LTD4, for the cells to levels 100-fold above their endogenous CysLT production. This suggests that cancer cells promote their own survival via LTD4 if supplied with LTC4, which in the exudates was produced by monocytic cells. Furthermore, exosomes promoted migration of cancer cells, which was counteracted by the CysLT1 antagonist montelukast. Montelukast also induced apoptosis of cancer cells, and this was partially inhibited by exosomes. Our results demonstrate how cancer cells and exosomes, together with monocytic cells in lung cancer tissue, can produce high amounts of LTD4, to stimulate cancer cell migration and survival. This suggests that part of the pro-metastatic effect of exosomes is mediated by the leukotriene machinery, further supporting the use of CysLT1 antagonists for lung cancer therapy. Highlights: Exosomes increase CysLTs formation by cancer cells. Exosomes promote migration/survival of cancer cells via CysLT1. Exosomes and cancer cells avidly transform LTC4 to LTD4, most potent agonist of CysLT1.